Management challenges in renal arteriovenous malformation mimicking AVF/pseudoaneurysm without trauma or pathological cause - Farzad Allameh; Niki Tadayon; Mohammad Amin Tofighi Zavareh; Seyed Mohammad SadrAmeli; Alvand Naserghandi (Urology Case Reports)
Renal arteriovenous malformations (AVMs) are rare and often pose diagnostic and management challenges, especially in the absence of trauma or underlying pathology. We report a case of a 33-year-old male with a long-standing renal artery aneurysm who presented with flank pain. Imaging revealed a high-flow renal AVM with multiple aneurysms, the largest measuring 30 mm. An attempted embolization was aborted due to the risk of pulmonary embolism. Open surgical repair was performed, involving ligation of the affected arterial branches. This case highlights the complexities in managing non-traumatic renal AVMs and the role of surgery when endovascular treatment is not feasible.